Mismatch in Children's Weight Assessment, Ideal Body Image, and Rapidly Increased Obesity Prevalence in China: A 10‐Year, Nationwide, Longitudinal Study. Issue 11 (3rd October 2018) - Min, Jungwon; Fang Yan, Alice; Wang, Youfa
Abstract : Objective: This study examined secular trends in children's weight‐status assessment, measured weight status, and ideal body image and their associations with subsequent changes in BMI, and it explored the differences between sociodemographic groups in China. Methods: Longitudinal data from the China Health and Nutrition Survey of 4, 605 children aged 6 to 17 collected between 2000 and 2011 were used and fitted to mixed models. Results: From 2000 to 2011, overweight/obesity prevalence increased from 6.5% to 16.8%, but the percentage of children with self‐perceived weight status as "fat" remained around 2.0%; 49.0% of children underestimated their weight status at baseline. Self‐perceived body image of most participants was tracked during follow‐up. Children who perceived themselves as being fat at baseline had a higher BMI increase over time during follow‐up than those with an average body image (β [SE] = 0.99 [0.14] kg/m 2 per year, P  < 0.001). Boys, young children, recent cohorts, and rural children had higher BMI increases than their counterparts. Over time, the thin‐body silhouette became more desirable (8.4 percentage points higher, P  < 0.001). Conclusions: Chinese children experience a large incongruence between their weight‐status assessment, ideal body image, and actual weight status. Health promotion programs should examine their role in assisting children in developing a healthy body image and gaining greater self‐motivation toward promoting a healthy lifestyle.